PENGARUH MOTIVASI, KOMPENSASI DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PENGELOLA KEARSIPAN YANG ADA DI LINGKUNGAN PEMERINTAH KABUPATEN OGAN KOMERING ILIR - Candra, Alek; Fatimah, Fatimah (MOTIVASI, 2020)
Purpose - This study aims to determine the effect of motivation, compensation and competence on the performance of records management employees in the Ogan Komering Ilir Regency  Government.Design/methodology - The design of this research is associative research by connecting between variables. The data used in this study are primary and secondary data, and respondents' answers are 120 employees  in  the  Government  of  Ogan  Komering  Ilir  Regency. The analytical method used is multiple linear regression and through testing the validity and reliability. Test data used to determine the characteristics of the data are the normality test and linearity test. The test model used consisted of multicollinity test and heterodecacity test, assisted by SPSS for windows version 22 with a significance level of  0.05.Findings - The results of multiple linear regression testing show compensation motivation and competence together have a significant influence on employee performance. Partially motivation has a positive and significant effect on employee performance, competence has a positive and significant effect on employee performance, while compensation has no positive and significant effect on employee performance.Implications: This study provides the results that motivation and competence are supporting factors for improving employee performance..